Electricity interdependence of members of the Southern African Development Community - Mokhethi, Keketso Elijah (My University, 2011)
The SADC region has been experiencing power shortages since 2007 and this has been more pronounced in South Africa, the biggest generator and consumer of electrical energy in the region. The power shortages have been primarily blamed on SADC governments‟ failure to invest in new power stations. In 2008 Eskom was forced to request its key customers (including those beyond the borders) to reduce their consumption by 10% in an effort to reduce electricity demand. Load shedding was also introduced as a way of Demand Side Management (DSM). Eskom is a major contributor in terms of supplying other countries with electricity in the Southern African Power Pool (SAPP). Therefore, any supply challenges it is facing will inadvertently affect the SAPP community. The SAPP is considering establishing a competitive cross-border electricity market where a buyer will have the freedom to purchase electricity from a supplier of their choice at a spot market rate. The study examines the extent to which SADC countries depend on each other for their electricity needs and the potential for a competitive cross-border electricity market given the current supply situation. A qualitative research methodology was used. Data collection was based on a questionnaire with the same questions asked to each respondent. The study found that SADC countries that participate in the SAPP depend on each other quite extensively for their electricity needs. The research also revealed that Eskom is the main player in the region as it trades electricity with many countries some of which depend on the South African utility for more than 50% of their domestic electricity needs. Another revelation of the study is that the SAPP utilities need to invest in generation and transmission capacity before a successful competitive cross-border electricity market can be operational. Security of supply and a reliable transmission network are crucial to the success of any power pool.
MBA - WBS
Keywords: Electricity supplies, Southern Africa; Electricity; Southern Africa Development Community